2003
DOI: 10.1016/s1535-6108(03)00303-9
|View full text |Cite
|
Sign up to set email alerts
|

A chemical genetic screen identifies inhibitors of regulated nuclear export of a Forkhead transcription factor in PTEN-deficient tumor cells

Abstract: The PI3K/PTEN/Akt signal transduction pathway plays a key role in many tumors. Downstream targets of this pathway include the Forkhead family of transcription factors (FOXO1a, FOXO3a, FOXO4). In PTEN null cells, FOXO1a is inactivated by PI3K-dependent phosphorylation and mislocalization to the cytoplasm, yet still undergoes nucleocytoplasmic shuttling. Since forcible localization of FOXO1a to the nucleus can reverse tumorigenicity of PTEN null cells, a high-content, chemical genetic screen for inhibitors of FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
270
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(285 citation statements)
references
References 55 publications
13
270
1
1
Order By: Relevance
“…Proteasome inhibitors MG132 and lactacystin were purchased from Sigma Chemical Co. (St Louis, MO) and were used at 5 (MG132) or 10 (lactacystin) mM for 12 h prior to cell harvesting. PI3-kinase inhibitor LY294002 (Sigma Chemical Co.) and Akt Inhibitor IV (compound 5233705, EMD Biosciences Inc., San Diego, CA) (Kau et al, 2003) were used at 4 and 50 mM concentrations, respectively, for 12 h prior to harvesting cells.…”
Section: Methodsmentioning
confidence: 99%
“…Proteasome inhibitors MG132 and lactacystin were purchased from Sigma Chemical Co. (St Louis, MO) and were used at 5 (MG132) or 10 (lactacystin) mM for 12 h prior to cell harvesting. PI3-kinase inhibitor LY294002 (Sigma Chemical Co.) and Akt Inhibitor IV (compound 5233705, EMD Biosciences Inc., San Diego, CA) (Kau et al, 2003) were used at 4 and 50 mM concentrations, respectively, for 12 h prior to harvesting cells.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis of phospho-proteins demonstrated that EGFR inhibition selectively blocked phosphorylation of ERK1/2 and RPS6 in cells with wt-VHL. The inhibition of RPS6 phosphorylation by Iressa, however, was not universal, which may relate to the presence of a PTEN mutation in 786-O and its derivatives (Kau et al, 2003). Mutant VHL lines showed little response to Iressa in terms of ERK and RPS6 phosphorylation and AKT phosphorylation was unaffected by either agent irrespective of VHL.…”
Section: Discussionmentioning
confidence: 93%
“…To investigate the role of Akt phosphorylation on PRAS40 activation, we administered Akt inhibitor IV (Calbiochem, San Diego, CA, USA), a cell-permeable benzimidazole compound that inhibits Akt phosphorylation by targeting the adenosine triphosphate binding site of a kinase upstream of Akt, but downstream of PI3K (Kau et al, 2003). Akt inhibitor IV was dissolved in DMSO PRAS40 protects motor neurons from death after SCI F Yu et al to make a stock solution of 10 mmol/L, and further diluted to 100 mmol/L in filtered PBS (pH 7.4) before use.…”
Section: Drug Injectionmentioning
confidence: 99%